Ocean Wave Measurement and Analysis (2001) 2002
DOI: 10.1061/40604(273)26
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Bathymetry Using Marine Radar Images of Waves

Abstract: This paper illustrates a method of calculating bathymetric maps of shallow water areas (<20m depth) using an analysis of wave properties determined from an analysis of marine radar image sequences of waves. Water depths determined using this corrected for tidal variation in water level are compared quantitatively to conventional surveys. Two case studies are shown from the COAST3D project field sites at Egmond aan Zee in the Netherlands and at Teignmouth in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…At Porthtowan, median depth estimates deviate more from the ground truth but remain ∆d < 2.0 m for depths d < 10 m (Figure 8b). Errors are largest in the breaking region where depths are d = 2 − 3 m, which is a common observation in depth inversion studies e.g., [92]. This is similar for Narrabeen (Figure 8d).…”
Section: Resultssupporting
confidence: 73%
“…At Porthtowan, median depth estimates deviate more from the ground truth but remain ∆d < 2.0 m for depths d < 10 m (Figure 8b). Errors are largest in the breaking region where depths are d = 2 − 3 m, which is a common observation in depth inversion studies e.g., [92]. This is similar for Narrabeen (Figure 8d).…”
Section: Resultssupporting
confidence: 73%
“…Although conceptually proven, these early developments were applied to limited datasets and lacked quantitative validation. Later, based on two single daily-averaged estimates from Egmond aan Zee (NL) and Teignmouth Pier (UK), Bell (2001) demonstrated that error margins could be within 1 m accuracy for depths up to 12 m, with exception of the breaker zone where errors were approximately 2 m.…”
Section: Introductionmentioning
confidence: 99%
“…Stockdon and Holman, 2000;Plant and Holman, 1997] or radars [e.g. Bell, 1999;Bell, 2001] have been employed for temporal coastal imaging supported by digital technologies and becoming popular for continuous monitoring. Video cameras can monitor sea surface patterns with high temporal resolution and can provide color images, which enable the detection of wave breaking, suspension of foams, sediment concentrations, etc.…”
Section: Aim Of the Studymentioning
confidence: 99%